ANALISIS KEMAMPUAN PEMECAHAN MASALAH SISWA SMA PADA MATERI SISTEM PERSAMAAN LINEAR - Agung Nugraha; Luvy Sylviana Zanthy (Journal on Education, 2018)
This study aims to determine the mathematical problem solving abilities of high school students based on the stage of understanding the problem, planning strategies, solving problems, and checking the answers obtained. The subjects of this study were students of class X MIA force 2018/2019 at the Sumur Bandung High School in 22 Bandung Barat regencies. The research used is qualitative descriptive method. The results of students are then analyzed based on the steps that are done. Based on the results of the analysis of students' mathematical problem solving abilities are still very low, especially at the stage of checking the answers obtained. Of the 22 students only 6 people were able to solve the questions properly and correctly, or 26.52% of the total students who took the test. So that it can be stated that the mathematical problem solving abilities of class X MIA students at Sumur Bandung High School are of low qualification, so the need for improvement and improvement efforts.